The prevalence of depression, anxiety and stress and their associated factors among Malaysian population : original research - Ong, Siew Chin; S, Shakeel; Ooi, GS (Pusat Perubatan Universiti Kebangsaan Malaysia, 2022)
The rising prevalence of mental disorders and their impact on the global disease burden is an emergent public health concern. The present study was to assess the prevalence of depression, stress and anxiety level among the Malaysian community by using Depression Anxiety and Stress Scale-21 (DASS-21) and identify their correlates by using the Belief of Depression Questionnaire (BDQ). The cross-sectional study was conducted among the Malaysian community through a convenient sampling method from October to December 2019. The DASS-21 and BDQ scales were used to explore the level of mental health and the respondents’ belief in their condition. The institutional ethics committee’s approval and participants’ written consent had been obtained before the commencement of the study. Spearman’s rank correlation coefficient was used to determine the association between the DASS scores. A total of 462 respondents were recruited into the study. The outcomes revealed that the respondents fell into mild stress levels (mean=14.5 + 10.3), moderate levels of anxiety (mean= 12.1 +±10.0), and mild levels of depression (mean=11.9 + 10.8). The majorly observed symptoms were tiredness (68.4%), reduced energy (46.8%), and dizziness (44.2%). Exercise (82.9%), spirituality (81.2%), and changing “how I think about myself” (79%) were the majorly reported factors considered helpful by the respondents to control or cure their condition. The study reported a higher prevalence of depression, stress, and anxiety among the younger age group, females, Indians, divorced/ unmarried, and lower monthly income respondents. Considering the results, it is essential to develop evidence-based and suitable community-based primary and secondary mental health prevention programmes.